Microbubbles for human diagnosis and therapy. (March 2023) - Fournier, Louise; de La Taille, Thibault; Chauvierre, Cédric
Abstract: Microbubbles (MBs) were observed for the first time in vivo as a curious consequence of quick saline injection during ultrasound (US) imaging of the aortic root, more than 50 years ago. From this serendipitous event, MBs are now widely used as contrast enhancers for US imaging. Their intrinsic properties described in this review, allow a multitude of designs, from shell to gas composition but also from grafting targeting agents to drug payload encapsulation. Indeed, the versatile MBs are deeply studied for their dual potential in imaging and therapy. As presented in this paper, new generations of MBs now opens perspectives for targeted molecular imaging along with the development of new US imaging systems. This review also presents an overview of the different therapeutic strategies with US and MBs for cancer, cardiovascular diseases, and inflammation. The overall aim is to overlap those fields in order to find similarities in the MBs application for treatment enhancement associated with US. To conclude, this review explores the new scales of MBs technologies with nanobubbles development, and along concurrent advances in the US imaging field. This review ends by discussing perspectives for the booming future uses of MBs.